2009
DOI: 10.1097/jcp.0b013e31819359be
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the LEP- and LEPR Gene and Obesity in Patients Using Antipsychotic Medication

Abstract: Weight gain is one of the most serious adverse effects of atypical antipsychotic agents. Genetic factors influence the risk of an individual to gain weight. The objective of our study was to determine whether the LEPR Q223R polymorphism and the LEP promoter 2548G/A polymorphism are associated with obesity in a group of male and female patients using atypical antipsychotic drugs. A cross-sectional study design was used. The study population consisted of 200 patients aged between 18 and 65 years, diagnosed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 42 publications
4
71
2
2
Order By: Relevance
“…Another study by Gregoor et al [52] found that baseline obesity risk was significantly greater for females carrying the LEPR 223R allele. This result runs contrary to the finding from their 2009 study which instead reported that the 223R allele was associated with lower baseline risk for female obesity [78]. …”
Section: Resultscontrasting
confidence: 56%
“…Another study by Gregoor et al [52] found that baseline obesity risk was significantly greater for females carrying the LEPR 223R allele. This result runs contrary to the finding from their 2009 study which instead reported that the 223R allele was associated with lower baseline risk for female obesity [78]. …”
Section: Resultscontrasting
confidence: 56%
“…8,[19][20][21][22][23][24][25][26][27][28] Evidence from large clinical samples indicates a high prevalence of metabolic dysfunction in people with serious mental illness, particularly in schizophrenic patients with nearly twice the normal risk of dying from cardiovascular disease. 29 High levels of medication non-compliance are present in a variety of psychiatric disorders, and metabolic side effects, in particular weight gain, could contribute in discontinuing antipsychotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We included children treated with only one antipsychotic medication (risperidone), all of whom were antipsychotic-naĂŻve at baseline, unlike other studies in which adults treated with a variety of antipsychotics were pooled into a single analysis [26,27,35,36]. This is the first report of associations of genetic markers with weight gain in Arab children and adolescents treated with risperidone.…”
Section: Discussionmentioning
confidence: 99%
“…This marker has also been associated with a measure of metabolic dysfunction, cholesterol/high density cholesterol ratio, in adult male patients using atypical antipsychotics who were at a relatively early phase (<1 year) of treatment [24]. Other studies in adults did not find any association between rs7799309 and obesity after 3 months of using antipsychotics [27], or weight gain after being on antipsychotics [28]. To our knowledge, only one study has examined rs7799309 and antipsychotic related weight gain in children and adolescents, and it reported that A allele carriers had steeper weight gain [17].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation